2005
DOI: 10.1007/s00432-005-0679-7
|View full text |Cite
|
Sign up to set email alerts
|

Accurate measurement of individual glomerular filtration rate in cancer patients: an ongoing challenge

Abstract: A narrow therapeutic index is a characteristic feature of cytotoxic agents. Some of these agents are almost entirely eliminated renally in unchanged active form. As a consequence, assessment of the individual glomerular filtration rate (GFR) may help to predict the pharmacokinetic behaviour of cytotoxic agents in plasma more precisely. In addition, GFR-adapted individualization of cancer chemotherapy may have an enormous impact on the severity of side effects. Several methods are available to determine GFR or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 49 publications
0
21
1
Order By: Relevance
“…Studies comparing serum CysC with eGFR measurements in patients with cancer have reported conflicting results but generally found CysC to perform better than serum Cr (7,8,(29)(30)(31). One adult HCT study evaluated CysC as a measure of renal function (31), finding that elevations in CysC did not correlate with serum Cr or Cr clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing serum CysC with eGFR measurements in patients with cancer have reported conflicting results but generally found CysC to perform better than serum Cr (7,8,(29)(30)(31). One adult HCT study evaluated CysC as a measure of renal function (31), finding that elevations in CysC did not correlate with serum Cr or Cr clearance.…”
Section: Discussionmentioning
confidence: 99%
“…48 There is some evidence that cystatin C concentrations are not affected by the presence of malignancies or inflammation. 49 On the other hand Kos et al have observed in their study a significant correlation between increased serum cystatin C and malignant progression in melanoma and colorectal cancer. 50 Demirtas et al conducted a study on 19 leukemic patients to evaluate the influence of malignancy and the impact of nephrotoxic drugs used in bone marrow transplantation (BMT) on the circulating levels of cystatin C in leukemia.…”
Section: Review Of Some Studies Examining Cystatin C As a Marker Of Rmentioning
confidence: 90%
“…Although creatinine clearance is a reliable marker in day-to-day practice in adults, its use in paediatrics has been questioned and there are situations where a more accurate measure of GFR is preferred Holweger et al, 2005). This information may be particularly important in clinical situations where potentially nephrotoxic drugs are administered, in addition to allowing for accurate renal function-based dosing of anticancer drugs such as carboplatin (Calvert et al, 1989;Holweger et al, 2005). It has been well established that the use of radioisotope tracers, such as 51 Cr-EDTA and 99m Tc-DTPA, are reliable methods for the accurate estimation of GFR (Rehling et al, 1984;Fawdry et al, 1985).…”
Section: Discussionmentioning
confidence: 99%